2016
DOI: 10.1371/journal.pone.0156695
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Extracellular DNA during Biofilm Formation by Xanthomonas citri subsp. citri Strains with Different Host Range

Abstract: Xanthomonas citri subsp. citri (Xcc) A strain causes citrus bacterial canker, a serious leaf, fruit and stem spotting disease of several Citrus species. X. alfalfae subsp. citrumelonis (Xac) is the cause of citrus bacterial spot, a minor disease of citrus nursery plants and X. campestris pv. campestris (Xc) is a systemic pathogen that causes black rot of cabbage. Xanthomonas spp. form biofilms in planta that facilitate the host infection process. Herein, the role of extracellular DNA (eDNA) was evaluated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 56 publications
(82 reference statements)
1
21
0
Order By: Relevance
“…eDNA has long been considered to be an integral part in bacterial biofilms (Okshevsky and Meyer 2015) but only recently shown to play a role in Xanthomonas biofilm formation. Specifically, Sena-Vélez and colleagues have shown that eDNA is highly abundant in Xanthomonas citri mature biofilm and accumulates throughout biofilm development (Sena-Vélez et al 2016). In addition, extracellular DNase treatment was able to inhibit biofilm formation but only partially dispersed mature biofilm, suggesting that eDNA plays a significant role in early stage of biofilm establishment (Sena-Vélez et al 2016).…”
Section: Attachment and Biofilm Formation On The Plant Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…eDNA has long been considered to be an integral part in bacterial biofilms (Okshevsky and Meyer 2015) but only recently shown to play a role in Xanthomonas biofilm formation. Specifically, Sena-Vélez and colleagues have shown that eDNA is highly abundant in Xanthomonas citri mature biofilm and accumulates throughout biofilm development (Sena-Vélez et al 2016). In addition, extracellular DNase treatment was able to inhibit biofilm formation but only partially dispersed mature biofilm, suggesting that eDNA plays a significant role in early stage of biofilm establishment (Sena-Vélez et al 2016).…”
Section: Attachment and Biofilm Formation On The Plant Surfacementioning
confidence: 99%
“…Specifically, Sena-Vélez and colleagues have shown that eDNA is highly abundant in Xanthomonas citri mature biofilm and accumulates throughout biofilm development (Sena-Vélez et al 2016). In addition, extracellular DNase treatment was able to inhibit biofilm formation but only partially dispersed mature biofilm, suggesting that eDNA plays a significant role in early stage of biofilm establishment (Sena-Vélez et al 2016). Other factors that were reported to be critical for Xanthomonas biofilm formation include cell surface LPS and lipoproteins (Li and Wang 2011a;Li and Wang 2011b;Petrocelli et al 2012;Yan, Hu and Wang 2012), the bacterial flagellum and type IV pili (Malamud et al 2011;Dunger et al 2014).…”
Section: Attachment and Biofilm Formation On The Plant Surfacementioning
confidence: 99%
“…Other biofilms formed by environmental microorganisms, plant pathogens (Sena-Velez et al 2016), or in the activated sludge during wastewater treatment have been studied to a lesser extent (e.g. Dominiak et al 2011).…”
Section: Biofilmsmentioning
confidence: 99%
“…These microcolonies are tightly packed bacteria, sometimes in regular hexagonal formation, separated by channels of water (Rigano et al, 2007). Xanthan and the presence of extracellular DNA are important during the early stages of biofilm formation (Rigano et al, 2007;Sena-V elez et al, 2016). The xanthan in the biofilm provides protection from both desiccation and plant antimicrobial compounds (Dow et al, 2003).…”
Section: Biofilm Formationmentioning
confidence: 99%